Analisis Faktor Kelelahan Kerja Pada Ojek Online Di Kota Batam - Wahyuda, Hendri; Zetli, Sri (LPPM Universitas Putera Batam, 2020)
Work fatigue is one of the problems in the field of occupational health and safety that can be a factor in workplace accidents. Lecturing activities, weakening motivation and physical weakness are the effects of fatigue. The purpose of this study was to determine the factors associated with work fatigue in online motorcycle taxis in Batam. Job fatigue data collection techniques with the IFRC Industrial Fatique Rating Committee questionnaire. In the results of the research questionnaire it was found that the most fatigue felt by online motorcycle taxi workers in Batam was 53 (76%) while those without 17 (24%), the average points on the weakening motivation questionnaire were 27 points, on average the weakening activity was 17 points while the average physical decline was 21 points. In this study there is a significant relationship between sex and length of work per day (hours) with work fatigue. While there is no significant relationship is age and length of work (years) with work fatigue. To reduce work fatigue on online motorcycle taxis in Batam, it is recommended to take a break together when the order is quiet, in addition to online motorcycle taxi breaks can be shared with other online motorcycle taxiworkers.